The Implementation of Sipakatau, Sipakainga, Sipakalebbi as Concept of Service by Local Community at Lae Lae Island, Makassar City - hayati, rafika; Sasmita, Anggun Sari; Achmadi, Nila Sartika (HOME : Hospitality and Gastronomy Research Journal, 2025)
Lae-lae as one of the nearest island from Makassar city with white sand and shady area. It loses the attractiveness as tourist destination because of construction around the Losari water front and culinary activities in Losari beach make the marine pollution. This research aim to develop the concept of local wisdom sipakatau, sipakainga and sipakalebbi which is life foundation of Buginese and Makassarese. Those concept implement in tourism service by local community to strengthen the character of local community. It is qualitative research with data collection technique by semi structured interview and questionaire. This research using semi structure interview and questionnaire distributed to tourists which described tourists' interpretations of local community services. The result of this research is implementation of local wisdom sipakatu, sipakainga and sipakalebbi implement in concept of tourism service by local community as part of culture from Makassarese. Sipakatau as part of the mutual appreciation form which emphasizes that there is no disparities between foreign and domestic tourists in term of service and price where both will receive what they have agreed with their providers. Sipakalebbi is adding smile, politeness, greetings and honesty to the services provided and Sipakainge is a tribute to local culture both by tourists. The development concept is expected to be the basis for represent the identity of the island